PEMANFAATAN TEPUNG UBI JALAR (Ipomea Btatas L) BERBAGAI VARIETAS SEBAGAI BAHAN BAKU PEMBUATAN KUE BOLU KUKUS - M Noer, Sri Wahyuni; Wijaya, Mohammad; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
This research aims to know the formulationsbolu kukus cake by using sweet potato flour and to know the varieties of sweet potatoes in the creation of bolu kukus cake. The research method using Random Complete. The results that it is processed using the techniques of analysis investigated a variety of ANOVA with a further DMRT (Duncan Multiple Rate). The results showed that most preferred by the panelists on the treatment A3Z3 with the formulation of flour 40% and sweet potato flour purple 60%